Negative active material particles encapsulated in pyrolyzed nanostructured magnesium oxide and methods of making and using same

The nanostructured magnesium oxide generated by pyrolysis coats carbon and/or silicon-based particles in lithium-ion batteries under shear conditions. Combined with surface modification technology, the problems of aging of negative electrode materials and uneven distribution of MgO particles are solved, and the problems of improved The cycle stability and life of the battery are achieved.

CN119318028APending Publication Date: 2025-01-14EVONIK OPERATIONS GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380044662.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-05-24
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, silicon-based negative electrode materials are easily formed in uncontrolled solid electrolyte interfaces during the initial charging-discharge process of the battery, resulting in material aging and performance loss. Nano-sized MgO particles are unevenly distributed on the surface of the negative electrode material, which affects the Battery life.

Method used

The nanostructured magnesium oxide produced by pyrolysis is coated with carbon and/or silicon-based particles under shear conditions by dry mixing, and the coverage and uniformity of the coating layer are further improved through surface modification to form a hydrophobic magnesium oxide package. Covering.

Benefits of technology

The uniform coating of the negative electrode material is achieved, the cycle stability and life of the battery is improved, the dispersion of MgO particles and the adhesion of the cladding layer are significantly improved, and the structural stability of the negative electrode active material is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005166852750000191
    Figure BDA0005166852750000191
  • Figure BDA0005166852750000201
    Figure BDA0005166852750000201
  • Figure BDA0005166852750000211
    Figure BDA0005166852750000211
Patent Text Reader

Abstract

A process for preparing a coated active anode material, wherein a mixed anode material and a nanostructured, preferably surface-modified magnesium oxide produced by pyrolysis are dry-blended by means of a mixing unit having a specific electrical power of 0.05-1.5 kW / kg of the mixed anode material. The coated mixed negative electrode material can be obtained by the method. A negative electrode for a lithium ion battery and a lithium ion battery comprising such a coated active negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing encapsulated negative electrode active material particles, wherein carbon and / or silicon-based particles and fumed nanostructured magnesium oxide are dry mixed under shear conditions. The present invention also relates to fumed magnesium oxide-coated negative electrode materials and battery cells containing encapsulated carbon and / or silicon-based negative electrode particles and uses thereof. Background Art

[0002] Various energy storage technologies have recently attracted much public attention and have been the subject of intensive research and development in industry and academia. As energy storage technology is extended to devices such as cellular phones, camcorders, and notebook PCs, and further to electric vehicles, the demand for high energy density batteries used as power sources for such devices is increasing. Secondary lithium-ion batteries are one of the most important types of batteries currently in use.

[0003] Secondary lithium-ion batteries are generally composed of a negative electrode (anode), such as a carbon material or a lithium-metal alloy, a positive electrode (cathode), such as a lithium-metal oxide, and an electrolyte, such as a lithium salt dissolved in an organic solvent. The separator of the lithium-ion battery provides a lithium ion channel between the positive and negative electrodes during the charge and discharge process of the battery.

[0004] U.S. Patent Application Publication 2019 / 0393543 describes a lithium metal secondary battery comprising a positive electrode, a negative electrode and a porous separator or electrolyte disposed between the positive electrode and the negative electrode, wherein the negative electrode comprises (a) a negative electrode active layer comprising a lithium or lithium alloy layer as a negative electrode active material in the form of a foil, a coating layer or a plurality of particles aggregated together, and (b) a negative electrode protective layer of a conductive sulfonated elastomer composite material disposed between the negative electrode active layer and the separator / electrolyte.

[0005] U.S. Patent Application Publication 2019 / 363345 describes forming a protective coating of graphene on a negative lithium metal electrode for a lithium-ion battery. The graphene protective coating is said to reduce dendrite growth.

[0006] International application publication WO2019215406A1 describes a negative electrode for a lithium ion battery, comprising at least one negative electrode material coated with a protective coating layer, the protective coating layer comprising a very long list of materials said to be suitable, however, neither the materials nor the methods disclosed in the present invention are disclosed therein.

[0007] Chinese patent application publication CN106025242A describes a composite negative electrode material for lithium-ion batteries, which includes a core layer of porous silicon alloy nanowires with carbon nanotubes and a shell layer made of a conductive polymer film blended with graphene, polypropylene oxide, polyethylene succinate, polysuccinic acid ester or polyethylene glycol imine.

[0008] Generally, coating cathode materials of lithium-ion batteries with metal oxides such as Al2O3, TiO2, ZrO2 and MgO has been described in the literature to improve the cycling performance.

[0009] Some examples of using MgO in negative electrode materials are provided in the following article. In an article entitled "Homogenizing Silicon Domains in SiOx Anode during Cycling and Enhancing Battery Performance via Magnesium Doping" published by Han et al. in ACS Appl. Mater. Interfaces 2021, 13, 52202-52214, magnesium is used as a dopant for SiOx negative electrode active materials. However, it takes temperatures above 1000°C to modify and react the components to ultimately form protective Mg-silicate compounds.

[0010] In an article entitled “Improvement of cycling performance of lithium-sulfur batteries by using magnesium oxide as a functional additive for trapping lithium polysulfide” published by Ponraj et al. in ACS Appl. Mater. Interfaces 2016, 8, 4000-4006, hydrophilic magnesium oxide was used as an additive for the active sulfur surface of the sulfur cathode to capture polysulfides.

[0011] In addition, generally, elements like carbon and its allotropes (graphene) have been used as negative electrode materials in lithium-ion secondary batteries, however, there are several problems with their structural stability. In an article entitled "An electrode comprising of graphene nano-powder inserted in an enclosed structure in anodic aluminum oxide coated with polyaniline by using low temperature hydrothermal process" published by Sugam et al. at the 62nd DAE Solid State Physics Symposium 1942, 1 in 2017, graphene nanopowder was inserted and confined on a negative electrode aluminum oxide coated with polyaniline.

[0012] In the article entitled “An Alumina-Coated Fe3O4-Reduced Graphene Oxide Composite Electrode as a Stable Anode for Lithium-ion Battery” published by Qi-Hui et al. in Electrochimica Acta (2015), 156, 147-153, an Al2O3 coating layer was used on the Fe3O4 reduced graphene oxide composite negative electrode material.

[0013] CN 103441252 discloses a lithium-rich negative electrode active material coated with nano-sized magnesium oxide.

[0014] In the article “Nanocrystalline NiO thin film anode with MgO coating for Li-ion batteries” published by Wang et al. in Electrochimica Acta (2003), Vol. 48, No. 28, pp. 4253-4259, a nanocrystalline NiO film was formed in an oxygen environment by pulsed laser reactive ablation, and then MgO was coated on the surface of the NiO film.

[0015] In “Rational formation of solid electrolyte interface for high-rate potassium ion batteries” published by Wang Bo et al. in Nano Energy, Vol. 75 (2020), p. 104979, a PS co-doped flexible carbon fiber film with SiO2 and MgO nanoparticles was synthesized.

[0016] A rather common problem of negative electrode materials, especially silicon-based negative electrode materials, is the formation of an uncontrolled solid electrolyte interface (SEI) during the initial charge-discharge process of the battery. In addition, aging processes within the bulk of the material lead to a loss of performance during cycling. This aging phenomenon is particularly relevant for Si-based negative electrode active materials. During the cycling process, the negative electrode materials are subject to several electrochemical degradation mechanisms. The deactivation of the negative electrode materials occurs through several electrochemical degradation mechanisms. The surface transformations caused by the electrolyte and the undesirable side reactions with the lithium species lead to the formation of an SEI layer with an increased thickness, which ultimately leads to reduced performance and battery life.

[0017] Surface coating has been demonstrated to be an extremely important approach to address the aging problem by inhibiting the direct contact between the active material surface and the liquid electrolyte.

[0018] Although nano-sized MgO particles have been used as additives in lithium-ion batteries, their effectiveness is limited by poor dispersibility. Practical methods for improving battery longevity are generally limited. Therefore, in the case of magnesium oxide, the use of commercially available nano-sized MgO particles generally results in uneven distribution and large agglomerated MgO particles on the surface of the negative electrode material (e.g., carbon and / or Si matrix material). As a result, the negative electrode material particles are not completely covered by the magnesium oxide particles, and it is clearly visible through SEM elemental mapping that large undispersed magnesium oxide particles are present, and the large undispersed magnesium oxide particles are located near the negative electrode particles.

[0019] The problem addressed by the present invention is to provide a uniform coating of metal oxides around carbon and / or Si-based particles produced by dry coating of powders.

[0020] Throughout the experimental process, it was surprisingly found that the pyrolytically produced nanostructured magnesium oxide can be successfully used for uniform coating of negative electrode materials such as carbon and / or Si-based particles using a dry mixing method for coating magnesium oxide on negative electrode materials. It was also surprisingly found that further surface modification of the pyrolytically produced nanostructured magnesium oxide before dry mixing can further significantly improve the coverage and uniformity of the coating. Summary of the invention

[0021] The present invention provides a method for preparing a coated active negative electrode material, the coated active negative electrode material and the use of the coated active negative electrode material in a lithium ion battery. The lithium ion battery of the present invention can be used in electronic and electrical equipment, including, for example, mobile phones, computers (laptop computers, desktop computers, tablet computers (computer pads)), electronic watches, remote control keys (key fabs), electrical appliances, power tools, vacuum cleaners, electric lawn mowers and electric vehicles.

[0022] According to a first aspect of the present invention, there is provided a method for preparing a coated active negative electrode material. The method is characterized in that the coated active negative electrode material is obtained by dry mixing the active negative electrode material and magnesium oxide produced by pyrolysis in a mixing unit under shear conditions, wherein the coated active negative electrode material is in the form of particles and the magnesium oxide has a particle size of 5-300 m 2 / g (DIN 9277: 2014) BET surface area, average aggregate diameter d 50 The particle size distribution is mono-modally and narrowly 5-150 nm, as determined by static light scattering (SLS) after sonicating a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25° C. for 60 s.

[0023] The pyrolytically produced MgO is hydrophilic. Preferably, in one embodiment, the pyrolytically produced MgO is surface modified to become hydrophobic.

[0024] In one embodiment, the hybrid unit has a specific electrical power of 0.05-1.5 kW / kg of mixed negative electrode material.

[0025] The coated active negative electrode material is in the form of particles, and the magnesium oxide has a particle size of 5-300 m 2 The BET surface area of ​​the particles is 5-150 nm, more preferably 10-120 nm, and even more preferably 20-100 nm, as measured by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt% of the particles and 95 wt% of a 0.5 g / L sodium pyrophosphate aqueous solution at 25°C for 60 s. 50 Unimodal and narrow particle size distribution.

[0026] In one embodiment, the method is characterized in that the specific electrical power of the mixing unit is 0.1-1000 kW and the volume of the mixing unit is 0.1 L to 2.5 m 3 , and the speed of the mixing tool in the mixing unit is 5-30m / s.

[0027] The span (d 90 -d 10 ) / d 50 0.4-1.2, as measured by static light scattering (SLS) after ultrasonication of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L aqueous sodium pyrophosphate solution at 25°C for 60 s.

[0028] The active negative electrode material includes carbon and / or silicon-based particles. As used herein, the term "silicon-based particles" refers to silicon particles (e.g., pure silicon particles), silicon oxide (SiOx) particles, and any combination of silicon, silicon oxide and carbon particles, including mixtures and composites thereof. Silicon oxide can be SiO and / or SiO2.

[0029] In one embodiment, the coated active negative electrode material is further heat treated after dry mixing.

[0030] In one embodiment, the proportion of magnesium oxide in the coated active negative electrode material is 0.05 wt% to 5 wt% based on the total weight of the coated mixed negative electrode material.

[0031] Another aspect of the present invention relates to a coated active negative electrode material obtainable by the above method.

[0032] According to another aspect of the present invention, there is provided a coated active negative electrode material, comprising an active negative electrode material and a coating layer of nanostructured magnesium oxide produced by pyrolysis on the surface of the mixed negative electrode material, wherein the coated active negative electrode material is in the form of particles, and the magnesium oxide has a particle size of 5-300 m 2 The BET surface area of ​​the particles is 1.3777:2014, and the average aggregate diameter d is determined by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25 ° C for 60 s. 50 The nanostructured magnesium oxide produced by pyrolysis is preferably surface treated to become hydrophobic by reacting the hydroxyl groups of MgO with silane to form -O-Si-R groups. The magnesium oxide is hydrophilic or hydrophobic, preferably hydrophobic. The active negative electrode material is carbon, silicon, silicon oxide (SiOx) or any combination thereof, including a mixture and / or a composite of carbon, silicon and silicon oxide.

[0033] SEM-EDX mapping of the coated active anode material provides complete and uniform coverage of pyrolytically produced MgO around substantially all anode particles, with no or only very few larger magnesium oxide agglomerates.

[0034] Other aspects of the present invention relate to active negative electrode materials for lithium ion batteries comprising the coated active negative electrode materials, further relate to lithium ion batteries comprising the coated active negative electrode materials, and further relate to the use of the coated active negative electrode materials in active negative electrode materials for lithium ion batteries.

[0035] Another aspect of the invention relates to a device powered by a lithium-ion battery.

[0036] Nanostructured magnesium oxide prepared by flame fusion has a single peak and narrow particle size distribution and excellent dispersibility during dry coating of negative electrode materials. These particles lead to excellent interaction and proper adhesion to negative electrode active materials.

[0037] Furthermore, the additional surface modification of these particles leads to further improvements in the interaction and adhesion with the negative electrode active material. This results in complete deagglomeration of the magnesium oxide agglomerates and ultimately provides negative electrode active material particles that are completely and uniformly covered with the gas phase processed, nanostructured and surface modified magnesium oxide.

[0038] It has been found that the method of the present invention results in significantly improved dispersibility and uniform coating of the MgO particles by using a high intensity dry coating method in combination with pyrolyzed, nanostructured MgO particles. During dry mixing, the applied shear forces (mixing) break up any MgO agglomerates into tiny aggregates which have a very high tendency to settle on the surface of the negative electrode active material particle powder, resulting in very good interaction and adhesion, which in turn results in a uniform coating. In contrast, conventional MgO particles, which are not pyrolyzed and nanostructured, consist of isolated spherical particles (which are the result of grinding coarser MgO particles) and do not show this behavior.

[0039] These and other features and advantages of the present invention will become better understood from the following detailed description taken in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 (a) shows the particle size distribution of nanostructured hydrophilic magnesium oxide produced by pyrolysis according to an embodiment of the present invention.

[0041] Figure 1 (b) shows the particle size distribution of conventional non-fumed magnesium oxide.

[0042] Figure 2 (a) shows an embodiment of the present invention, coated on the negative electrode active material Figure 1 (a) SEM-EDX mapping of the pyrolysis-produced nanostructured hydrophilic MgO.

[0043] Figure 2 (b) shows a SEM-EDX mapping of pyrolysis-generated nanostructured and surface-modified magnesium oxide coated on a negative electrode active material according to an embodiment of the present invention.

[0044] Figure 2 (c) shows the coating on the negative electrode active material as a comparative example Figure 1 (b) SEM-EDX mapping of non-fumed MgO.

[0045] Figure 3 A lithium-ion battery is shown within a device according to an embodiment of the present invention. DETAILED DESCRIPTION

[0046] According to a first aspect of the present invention, there is provided a method for preparing encapsulated active negative electrode material particles, wherein the active negative electrode material is dry mixed with fumed, nanostructured, and preferably also surface-modified magnesium oxide under shear conditions. A second aspect of the present invention relates to a negative electrode material coated with fumed magnesium oxide, and a third aspect of the present invention relates to a battery cell comprising encapsulated carbon and / or silicon-based negative electrode particles.

[0047] Method for preparing coated negative electrode active material

[0048] According to a first aspect of the present invention, there is provided a method for preparing a coated active negative electrode material, wherein carbon and / or Si-based negative electrode particles and pyrolysis-generated nanostructured and preferably surface-modified magnesium oxide are dry mixed under shear conditions. The silicon-based negative electrode particles include silicon particles, silicon oxide particles, and any combination of silicon, silicon oxide and carbon particles.

[0049] The fumed nanostructured magnesium oxide is also preferably surface modified to become hydrophobic prior to dry blending.

[0050] The active negative electrode material may also be referred to as the core active negative electrode material or the matrix active negative electrode material or particles. The nanostructured and preferably surface-modified MgO produced by pyrolysis may also be referred to as a coating. Coated active negative electrode material refers to a mixed active negative electrode material with a coating produced by dry mixing. Once dry mixing is completed, the carbon and / or Si-based particles are covered with MgO.

[0051] Dry Mix

[0052] Dry mixing can be carried out, for example, in a mixing unit with a specific electrical power of 0.05-1.5 kW / kg of mixed negative electrode material. Dry mixing is understood to mean that no liquid is added or used during the mixing process, i.e., for example, substantially dry powders are mixed together. However, trace amounts of moisture or some liquid other than water may be present in the mixed raw materials, or these may include water of crystallization.

[0053] If the specific electrical power used is less than 0.05 kW / kg of mixed negative electrode material, this produces an uneven distribution of magnesium oxide on the top of the negative electrode active material particles, which may not be firmly bound to the core material of the negative electrode active material particles. A specific electrical power of more than 1.5 kW per kilogram of mixed negative electrode material leads to poor electrochemical properties. In addition, there is a risk that the coating becomes brittle and easy to break. The nominal electrical power of the hybrid unit can vary over a wide range, for example from 0.1 kW to 1000 kW. Therefore, a laboratory-scale hybrid unit with a nominal power of 0.1-5 kW or a production-scale hybrid unit with a nominal electrical power of 10-1000 kW can be used. The nominal electrical power is the maximum absolute electrical power on the nameplate of the hybrid unit.

[0054] The volume of the mixing unit can vary within a wide range. For example, the volume of the mixing unit can range from 0.1 L to 2.5 m 3 For example, a laboratory scale mixing unit may have a volume of 0.1-10 L, or a production scale mixing unit may have a volume of 0.1-2.5 m 3 volume.

[0055] Preferably, in the process according to the invention, the forced action mixer is used in the form of an intensive mixer with high-speed mixing tools. It has been found that the speed of the mixing tools is 5-30 m / s, more preferably 10-25 m / s, to obtain the best results. Examples of commercially available mixing units suitable for the process according to the invention include Henschel mixers and Eirich mixers. For example, the Eirich mixer can be a high-intensity Eirich mixer.

[0056] The mixing time may vary and may preferably be from 0.1 to 120 min, more preferably from 0.2 to 60 min, and most preferably from 0.5 to 10 min.

[0057] After mixing, the mixture may be subjected to a heat treatment to improve the bonding of the coating layer to the negative electrode active material particles. However, this treatment is optional in the method according to the invention, because in this method, the pyrolytically produced, nanostructured and surface-modified magnesium oxide adheres firmly enough to the core negative electrode active material particles, i.e., carbon and / or silicon-based particles. Therefore, a preferred embodiment of the method of the invention may not include a heat treatment after mixing.

[0058] It has been found that when magnesium oxide has 5m 2 / g-300m 2 / g, more preferably 10m 2 / g-200m 2 / g and most preferably 15-150m 2The best results regarding the adhesion of magnesium oxide to the core negative electrode active material particles were obtained when the BET surface area was 1000 Å / g. The BET surface area can be determined according to DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller procedure.

[0059] Formation of MgO by thermal decomposition

[0060] The magnesium oxide used in the method according to the invention is pyrolytically produced, i.e. produced by a pyrolysis process. Pyrolysis processes are also called "gas phase" processes. Such "pyrolysis" or "gas phase" processes involve the reaction of the corresponding metal precursors to form metal oxides in a flame hydrolysis or flame oxidation in a hydrogen-oxygen flame.

[0061] A hydrophilic magnesium oxide prepared by pyrolysis, characterized by:

[0062] Surface area [m 2 / g]50 to 350

[0063] Tamped density [g / L] 20 to 100

[0064] Drying loss [%] less than 5

[0065] Loss on ignition [%] 0.1 to 20

[0066] The terms "pyrolytically produced or prepared", "pyrolytic" and "gas phase process" are used equivalently in the context of the present invention. Fumed magnesium oxide can be prepared by flame hydrolysis or flame oxidation. This involves the oxidation or hydrolysis of a hydrolyzable or oxidizable raw material, usually in a hydrogen / oxygen flame. The raw materials typically used in the pyrolytic process include organic or inorganic substances, such as metal chlorides.

[0067] Thus, the hydrophilic magnesium oxide according to the present invention can be prepared by flame spray pyrolysis, wherein at least one solution of a metal precursor comprising a magnesium salt, a solvent such as ethanol, methanol or water is subjected to flame spray pyrolysis.

[0068] In flame spray pyrolysis, a solution of metal compounds (metal precursors) is generally introduced in the form of fine droplets into a flame formed by ignition of fuel gas and oxygen-containing gas, wherein the metal precursors used are oxidized and / or hydrolyzed to give the corresponding magnesium oxide.

[0069] The reaction initially forms highly dispersed approximately spherical primary particles, which coalesce to form aggregates in the further process of the reaction. The aggregates can then aggregate into agglomerates. Contrary to the agglomerates that can be relatively easily separated into aggregates by introducing energy, if the aggregates are to be further decomposed, only the strong introduction of energy is required. The metal oxide powder can be partially destroyed and converted into particles in the nanometer (nm) range that are conducive to the present invention by suitable grinding.

[0070] The resulting aggregate compound may be referred to as "fumed" or "pyrolytically produced" magnesium oxide.

[0071] Flame spray pyrolysis processes are generally described in WO 2015173114 A1 and elsewhere.

[0072] The flame spray pyrolysis method of the present invention preferably comprises the following steps:

[0073] a) atomizing a solution of a metal precursor by means of an atomizer gas to provide an aerosol,

[0074] b) reacting the aerosol in the reaction space of the reactor with a flame obtained by igniting a mixture of a fuel gas and an oxygen-containing gas to obtain a reaction stream,

[0075] c) cooling the reaction stream, and

[0076] d) subsequently removing the solid magnesium oxide from the reaction stream.

[0077] The metal precursor used in the method of the present invention includes a magnesium salt such as magnesium chloride, magnesium nitrate or magnesium acetate.

[0078] The solvent of the solution may be all typical solvents, such as water, ethanol, methanol and the like.

[0079] The amount of the metal precursor in the solution may be 5-80 wt %, preferably 20-70 wt %, based on the total weight of the solution.

[0080] Examples of fuel gases are hydrogen, methane, ethane, natural gas and / or carbon monoxide. Particular preference is given to using hydrogen.

[0081] The oxygen-containing gas is typically air or oxygen-enriched air. The oxygen-containing gas is particularly useful in embodiments requiring a high BET surface area of, for example, magnesium oxide to be produced. The total amount of oxygen is typically selected so that it is sufficient for at least complete conversion of the fuel gas and the metal precursor.

[0082] In order to obtain an aerosol, the vaporized solution containing the metal precursor can be mixed with an atomizer gas such as nitrogen, air and / or other gases. The resulting fine droplets of the aerosol preferably have an average droplet size of 1-120 μm, particularly preferably 30-100 μm. The droplets are usually produced using a single material or multi-material nozzle. In order to increase the solubility of the metal precursor and obtain a suitable viscosity for solution atomization, the solution can be heated.

[0083] The particle size of magnesium oxide can be varied by reaction conditions such as flame temperature, hydrogen or oxygen ratio, amount of magnesium salt, residence time in the flame or length of the condensation zone.

[0084] The metal oxide precursor used can be dissolved in water or an organic solvent by atomization. Suitable organic solvents include methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, 2-acetone, 2-butanone, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, C1-C8-carboxylic acid, ethyl acetate, toluene, petroleum and mixtures thereof.

[0085] Thus, the pyrolytically produced nanostructured and preferably surface-modified magnesium oxide used in the process according to the invention is in the form of aggregated primary particles, preferably having a numerical average aggregate diameter of 5-150 nm, more preferably 10-120 nm, even more preferably 20-100 nm, as determined by transmission electron microscopy (TEM). The numerical average diameter can be determined by calculating the average size of at least 500 particles analyzed by TEM.

[0086] The average diameter of the agglomerates is generally 1-2 μm. These average values ​​can be determined in a suitable dispersion, for example in an aqueous dispersion, by a static light scattering (SLS) method. Agglomerates and partial aggregates can be broken down to produce particles with a smaller particle size, for example by grinding or ultrasonic treatment of the particles.

[0087] The average aggregate diameter of metal oxides 50 5-150 nm, more preferably 10-120 nm, even more preferably 20-100 nm, as measured by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25°C for 60 s.

[0088] Therefore, the nanostructured and preferably surface-modified magnesium oxide produced by pyrolysis for the method of the present invention is preferably characterized by high dispersibility, i.e., the ability to form smaller particles under mild ultrasonic treatment. It is believed that the dispersion under such mild conditions is related to the conditions in the dry coating process. This means that the agglomerates of magnesium oxide are destroyed in a similar manner to that under ultrasonic treatment during the mixing process of the present invention, and a uniform coating of the negative electrode active material particles can be formed.

[0089] The span of magnesium oxide particles (d 90 -d 10 ) / d 50 Preferably it is 0.4-1.2, more preferably 0.5-1.1, even more preferably 0.6-1.0, as measured by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt% of the particles and 95 wt% of a 0.5 g / L sodium pyrophosphate aqueous solution at 25°C for 60 s.

[0090] Therefore, the pyrolytically produced nanostructured magnesium oxide used in the method of the present invention is preferably characterized by a relatively narrow particle size distribution. This helps to obtain a high-quality magnesium oxide coating on the surface of the negative electrode material particles.

[0091] d value 10 ,d 50 and d 90 It is often used to characterize the cumulative particle size distribution of a given sample. For example, d 10 The diameter is 10% of the sample volume by less than d 10 The diameter of the particles, d 50 50% of the sample volume is smaller than d 50 The diameter of the particles. 50 Also called the “volume median diameter” because it divides the sample equally by volume; d 90 90% of the sample volume is smaller than d 90 The diameter of the particles when they are composed.

[0092] Magnesium oxide produced by pyrolysis is hydrophilic. By surface modification of the magnesium oxide produced by pyrolysis, hydrophobic magnesium oxide is then produced. The surface treatment may include the use of any of a number of suitable hydrophobic agents, such as silanes. Both hydrophilic and hydrophobic forms of gas phase nanostructured magnesium oxide can be used as coatings by dry mixing with a matrix active negative electrode material using the method of the present invention. However, gas phase, nanostructured and surface modified hydrophobic magnesium oxide is preferred because it shows more uniform coverage of the matrix active negative electrode material and complete coverage of the matrix active negative electrode material.

[0093] Surface treatment of pyrolytically produced MgO.

[0094] The pyrolytically produced MgO without any further surface treatment is hydrophilic because it is naturally covered with hydroxyl (-OH) groups. However, by surface modification of the pyrolytically produced MgO, hydrophobic MgO is also produced. For example, hydrophobization of MgO can be performed by reacting the hydroxyl groups with silanes to form -O-Si-R groups. Therefore, preferably, the MgO is surface modified, which means that the surface of the MgO is at least partially covered with silanes.

[0095] The MgO produced by pyrolysis can be used in its hydrophilic and hydrophobic forms. The use of hydrophilic MgO does not require any further treatment after synthesis by the pyrolysis method. However, after synthesis by the pyrolysis method, the MgO particles can be made hydrophobic by further treatment with a hydrophobic agent such as silane. For example, in one embodiment, octylsilane is covalently bound to the surface of the MgO particles. Using the method of the present invention, both the hydrophilic and hydrophobic forms of the gas-phase nanostructured MgO can be effectively used as a coating layer by dry mixing with the base active negative electrode material. Gas-phase nanostructured and surface-modified MgO is preferred because it shows a more uniform coverage of the base active negative electrode material.

[0096] In one embodiment, a pyrolytically prepared surface-modified magnesium oxide is prepared, characterized in that:

[0097] Surface area [m 2 / g]50 to 350

[0098] Tamped density [g / L] 20 to 100

[0099] Drying loss [%] less than 5

[0100] Loss on ignition [%] 0.1 to 20

[0101] Thus, the pyrolytically prepared magnesium oxide is sprayed with a surface modifier at room temperature and the mixture is subsequently heat treated at a temperature of 50-300° C., preferably 80-180° C., for 0.5-3 hours (“h”).

[0102] In an alternative embodiment, surface modification of the pyrolytically prepared magnesium oxide may be performed by treating the pyrolytic magnesium oxide with a surface modifier in vapor form and subsequently heat treating the mixture at a temperature of 50 to 800° C. for a period of 0.5 to 6 h.

[0103] An alternative method for surface modification of pyrogenically prepared magnesium oxide may be carried out by treating the pyrogenic magnesium oxide with a surface modifier in vapor form and subsequently heat treating the mixture at a temperature of 50 to 800° C. for a period of 0.5 to 6 h.

[0104] The heat treatment can be carried out under a protective gas such as nitrogen. The surface treatment can be carried out continuously or batchwise in a heatable mixer and dryer with a spray device. Suitable devices can be, for example, a ploughshare mixer or plate, a cyclone separator or a fluidized bed dryer.

[0105] An advantage of the present invention is that commercially available silanes can be used to modify the magnesium oxide and thus individually adjust the properties of the magnesium oxide according to the desired properties and the intended purpose.

[0106] As surface modifiers, the following compounds and mixtures of the following compounds may be used:

[0107] a)(RO)3Si(C n H 2n+1 ) and (RO)3Si(C n H 2n-1 ) type organosilane, wherein R = alkyl, such as methyl, ethyl, n-propyl, isopropyl, butyl, and n = 1-20,

[0108] b) R' x (RO) y Si(C n H 2n+1 ) and R' x (RO) y Si(C n H 2n-1 ) type organosilane, wherein

[0109] R = alkyl, such as methyl-, ethyl-, n-propyl-, isopropyl-, butyl-

[0110] R' = alkyl, such as, for example, methyl, ethyl, n-propyl, isopropyl, butyl

[0111] R'=cycloalkyl

[0112] n=1-20

[0113] x+y=3

[0114] x = 1, 2, and

[0115] y=1,2

[0116] c)X3Si(C n H 2n+1 ) and X3Si(C n H 2n-1 ) type of halogenated organosilane, wherein

[0117] X=Cl,Br

[0118] n=1-20

[0119] d)X2(R')Si(C n H 2n+1 ) and X2(R')Si(C n H 2n-1 ) type of halogenated organosilane, wherein

[0120] X=Cl,Br

[0121] R' = alkyl, such as, for example, methyl, ethyl, n-propyl, isopropyl, butyl

[0122] R'=cycloalkyl

[0123] n=1-20

[0124] e)X(R')2Si(C n H 2n+1 ) and X(R')2Si(C n H 2n-1 ) type of halogenated organosilane, wherein

[0125] X=Cl,Br

[0126] R' = alkyl, such as, for example, methyl, ethyl, n-propyl, isopropyl, butyl

[0127] R'=cycloalkyl

[0128] n=1-20

[0129] f)(RO)3Si(CH2) m -R' type organosilicon

[0130] R = alkyl, such as methyl, ethyl, propyl

[0131] m=0.1-20

[0132] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , -O-CF2-CHF2, -NH2, -N3, -SCN, -CH=CH2, -NH-CH2-CH2-NH2, -N-(CH2-CH2-NH2)2, -OOC(CH3)C=CH2 , -OCH2-CH(O)CH2, -NH-CO-N-CO-(CH2)5, -NH-COO-CH3, -NH-COO-CH2-CH3, -NH-(CH2)3Si(OR)3, -S x -(CH2)3Si(OR)3, -SH, -NR'R"R"'

[0133] R'=alkyl, aryl;

[0134] R"=H, alkyl, aryl;

[0135] R"'=H, alkyl, aryl, benzyl, C2H4NR""R""'wherein R""=H, alkyl and

[0136] R""'=H, alkyl

[0137] g)(R") x (RO) y Si(CH2)m-R' type organosilane

[0138] R"=alkyl

[0139] x+y=2

[0140] = Cycloalkyl x = 1.2

[0141] y=1.2

[0142] m=0.1 to 20

[0143] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , -O-CF2-CHF2, -NH2, -N3, -SCN, -CH=CH2, -NH-CH2-CH2-NH2, -N-(CH2-CH2-NH2)2, -OOC(CH3)C=CH2 , -OCH2-CH(O)CH2, -NH-CO-N-CO-(CH2)5, -NH-COO-CH3, -NH-COO-CH2-CH3, -NH-(CH2)3Si(OR)3, -S x -(CH2)3Si(OR)3, -SH, -NR'R"R"'

[0144] R'=alkyl, aryl;

[0145] R"=H, alkyl, aryl;

[0146] R"'=H, alkyl, aryl, benzyl, C2H4NR""R""'wherein R""=H, alkyl and

[0147] R""'=H, alkyl

[0148] h) X3Si(CH2)m-R' type halogenated organosilane

[0149] X=Cl,Br

[0150] m=0.1-20

[0151] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , -O-CF2-CHF2, -NH2, -N3, -SCN, -CH=CH2, -NH-CH2-CH2-NH2, -N-(CH2-CH2-NH2)2, -OOC(CH3)C=CH2 , -OCH2-CH(O)CH2, -NH-CO-N-CO-(CH2)5, -NH-COO-CH3, -NH-COO-CH2-CH3, -NH-(CH2)3Si(OR)3, -S x-(CH2)3Si(OR)3, -SH

[0152] i) (R)X2Si(CH2)m-R' type halogenated organosilicon

[0153] X=Cl,Br

[0154] R = alkyl, such as methyl, ethyl, propyl

[0155] m=0.1-20

[0156] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , -O-CF2-CHF2, -NH2, -N3, -SCN, -CH=CH2, -NH-CH2-CH2-NH2, -N-(CH2-CH2-NH2)2, -OOC(CH3)C=CH2 , -OCH2-CH(O)CH2, -NH-CO-N-CO-(CH2)5, -NH-COO-CH3, -NH-COO-CH2-CH3, -NH-(CH2)3Si(OR)3, -S x -(CH2)3Si(OR)3, -SH,

[0157] j) (R)2X Si(CH2)m-R' type halogenated organosilane

[0158] X=Cl,Br

[0159] R=alkyl

[0160] m=0.1-20

[0161] R' = methyl-, aryl (e.g., -C6H5, substituted phenyl residue), C4F9, OCF2-CHF-CF3, -C6F 13 , -O-CF2-CHF2, -NH2, -N3, -SCN, -CH=CH2, -NH-CH2-CH2-NH2, -N-(CH2-CH2-NH2)2, -OOC(CH3)C=CH2 , -OCH2-CH(O)CH2, -NH-CO-N-CO-(CH2)5, -NH-COO-CH3, -NH-COO-CH2-CH3, -NH-(CH2)3Si(OR)3, -S x -(CH2)3Si(OR)3, -SH

[0162] Preferably, as surface modifiers, the following silanes are used alone or in a mixture: dimethyldichlorosilane, octyltrimethoxysilane, octyltriethoxysilane, hexamethyldisilazane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, dimethylpolysiloxane, glycidyloxypropyltrimethoxysilane, glycidyloxypropyltriethoxysilane, nonafluorohexyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, aminopropyltriethoxysilane. Particularly preferably, octyltrimethoxysilane and octyltriethoxysilane can be used.

[0163] The MgO particles produced by the pyrolysis process generally have a purity of at least 96 wt%, preferably at least 98 wt%, more preferably at least 99 wt%. The magnesium oxide used in the process of the invention preferably contains the elements Cd, Ce, Fe, Na, Nb, P in a proportion of <10 ppm and the elements Ba, Bi, Cr, K, Mn, Sb in a proportion of <5 ppm, wherein the sum of the proportions of all these elements is <100 ppm. The proportion of carbon in the hydrophilic non-surface-modified metal oxide is preferably less than 0.2 wt%, more preferably 0.005-0.2 wt%, even more preferably 0.01-0.1 wt%, based on the mass of the metal oxide powder.

[0164] Active negative electrode material

[0165] The matrix negative electrode particles encapsulated or coated with gas phase MgO may include any suitable material used as a negative electrode active material in a secondary lithium ion battery, which can reversibly insert / deintercalate lithium ions and / or reversibly react with lithium substances. Examples thereof are carbonaceous materials, including crystalline carbon, such as natural or artificial graphite in the form of plate-like, flaky, spherical or fibrous graphite; amorphous carbon, such as soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc., or mixtures thereof. In addition, Si-based particles can be used as negative electrode active materials. Preferred negative electrode active materials are carbon and / or silicon-based particles. Silicon-based particles include silicon particles (e.g., pure silicon particles), silicon oxide (SiOx) particles, and any combination of silicon, silicon oxide and carbon particles, including mixtures and composites thereof. Silicon oxide can be SiO and / or SiO2. In one embodiment, the active negative electrode material can be a nanostructured porous silicon material. In one embodiment, the negative electrode material is SiOx, where x can be from 0 to about 2, such as Si, SiO, SiO2, or any combination thereof.

[0166] Preferred negative electrode active materials are carbon and / or Si-based particles, including composite materials of C and Si-based particles. "Composite material" refers to a composition comprising both carbon material and silicon material. The carbon and silicon materials can be a mixture of carbon powder and silicon powder of nano-sized particles. In one embodiment, the composite material can include a single particle of chemically bonded carbon and silicon. In another embodiment, the composite material can include porous nano-sized silicon particles, wherein carbon is impregnated in a silicon porous structure.

[0167] The active negative electrode material mixed and coated with metal oxides may include carbon and / or Si-based particles. In some embodiments, the active negative electrode material may include a composite SiOx / C material, wherein x may vary from 0 to about 2, made of 60-99% carbon and 40-1% silicon oxide, preferably 70-95% carbon and 30-5% silicon oxide, more preferably 80-90% carbon and 20-10% silicon oxide. The composite SiOx / C material may be in the form of a powder or granules.

[0168] In one embodiment, the active negative electrode material may include a composite SiO / C material made of 60-99% carbon and 40-1% SiO, preferably 70-95% carbon and 30-5% SiO, more preferably 80-90% carbon and 20-10% SiO. The composite SiO / C material may be in the form of powder or granules.

[0169] In some embodiments, the active negative electrode material may include a composite Si / C material made of 60-99% carbon and 40-1% silicon, preferably 70-95% carbon and 30-5% silicon, more preferably 80-90% carbon and 20-10% silicon. The composite Si / C material may be in the form of powder or granules.

[0170] The numerical average particle size of the coated active negative electrode material is 1-50 μm, preferably 1-40 μm, and more preferably 2-20 μm. The numerical average particle size can be measured by laser diffraction particle size analysis according to ISO 13320:2009.

[0171] The active negative electrode material may also be referred to as a core active negative electrode material or a matrix active negative electrode material or particle. MgO may also be referred to as a coating layer, and the mixed active negative electrode material with the coating layer may also be referred to as a coated active negative electrode material or particle.

[0172] Based on the total weight of the coated mixed negative electrode material, the proportion of magnesium oxide in the coated mixed negative electrode material is preferably 0.05wt%-5wt%, more preferably 0.1wt%-2wt%. If the proportion of magnesium oxide is less than 0.05wt%, the beneficial effect of the coating layer is generally still not observed. In the case where it exceeds 5wt%, the beneficial effect of the additional amount of magnesium coating layer exceeding 5wt% is generally not observed.

[0173] The coated mixed negative electrode material preferably has a coating layer thickness of 10 to 200 nm as determined by TEM analysis.

[0174] The present invention further provides a coated hybrid negative electrode material obtainable by the method of the present invention. The present invention also provides a coated hybrid negative electrode material comprising a pyrolytically generated, nanostructured and surface-modified magnesium oxide coating layer on the surface of the negative electrode active material particles.

[0175] The further preferred features of the coated hybrid negative electrode material, pyrolytically produced, nanostructured and surface-modified magnesium oxide described in the above preferred embodiments of the method according to the present invention also relate to the coated hybrid negative electrode material, pyrolytically produced, nanostructured and surface-modified magnesium oxide according to the present invention, regardless of whether it is prepared by the method of the present invention.

[0176] The present invention further provides an active negative electrode material for a lithium ion battery, comprising a coated negative electrode material according to the invention or a coated negative electrode material obtainable by a process according to the invention.

[0177] The negative electrode, i.e., the negative electrode of a lithium-ion battery, includes a current collector and coated active negative electrode material particles formed on or above the current collector. The current collector can be, for example, aluminum foil, copper foil, nickel foil, stainless steel foil, titanium foil, a polymer matrix coated with a conductive metal, or a combination thereof.

[0178] The present invention also provides a lithium ion battery comprising a coated negative electrode material or a coated negative electrode material obtainable by the method according to the present invention.

[0179] In addition to the negative electrode, the lithium ion battery of the present invention may also include a positive electrode, an optional separator and an electrolyte including, for example, a lithium salt or a lithium compound.

[0180] The positive electrode of the lithium ion battery may include any suitable material that is commonly used in lithium ion secondary batteries and is capable of reversibly intercalating / deintercalating lithium ions.

[0181] The positive electrode material preferably used in the method according to the invention is selected from lithium-cobalt oxide, lithium-manganese oxide, lithium-nickel-cobalt oxide, lithium-nickel-manganese-cobalt oxide, lithium-nickel-cobalt-aluminum oxide, lithium-nickel-manganese oxide and mixtures thereof.

[0182] The electrolyte of the lithium-ion battery can be in liquid, gel or solid form. The liquid electrolyte of the lithium-ion battery can include any suitable organic solvent commonly used in lithium-ion batteries, such as anhydrous ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate, ethyl methyl carbonate, diethyl carbonate, γ-butyrolactone, dimethoxyethane, fluoroethylene carbonate, vinyl ethylene carbonate and mixtures thereof.

[0183] The gel electrolyte includes a gelling polymer. Any suitable gelling polymer may be used.

[0184] Solid electrolytes for lithium-ion batteries may include oxides, such as lithium metal oxides, sulfides, phosphates, or solid polymers.

[0185] The electrolyte of the lithium-ion battery may include a lithium salt. Examples of such lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis[2-(trifluoromethanesulfonyl)imide] (LiTFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium trifluoromethanesulfonate, LiN(SO2CF2CF3)2, and mixtures thereof.

[0186] The present invention further provides use of the coated negative electrode material in an active negative electrode material of a lithium ion battery.

[0187] Even without further explanation, it is assumed that one skilled in the art can fully utilize the above description.Therefore, the preferred embodiments and examples should be construed as merely descriptive and not limiting in any way.

[0188] Hereinafter, the present invention is explained in more detail using examples.Alternative embodiments of the present invention can be obtained in a similar manner.

[0189] Example:

[0190] Determination of physicochemical characteristic data

[0191] In the context of the present invention, the following measurement methods for evaluating the properties of different materials are used:

[0192] A) BET surface area:

[0193] The BET surface area was determined with nitrogen according to DIN 9277:2014.

[0194] B) Compacted density:

[0195] Determination of the tamped density according to an adaptation of DIN ISO 787 / XI,

[0196] Basic principles of tamped density determination:

[0197] The tamped density (formerly tamped volume) is equal to the quotient of the mass and volume of the powder after tamping in a tamping volumeter under the prescribed conditions. According to DIN ISO 787 / XI, the tamped density is expressed in g / cm 3 However, since the tamped density of the oxide is very low, we give the value in g / L. In addition, the drying and sieving as well as the repetition of the tamping operation are omitted.

[0198] Equipment for measuring compacted density:

[0199] Compaction volume meter

[0200] Graduated Cylinder

[0201] Laboratory scale (reading accuracy 0.01g)

[0202] To perform a tamped density determination:

[0203] 200 ± 10 mL of oxide is filled into the graduated cylinder of the compacting volumeter in such a way that no pores are left and the surface is level. The mass of the filled sample is accurately determined to 0.01 g. The graduated cylinder with the sample is placed in the graduated cylinder holder of the compacting volumeter and compacted 1250 times. The volume of the compacted oxide is accurately read once.

[0204] Evaluation of compacted density determination

[0205]

[0206] C) pH value:

[0207] The pH values ​​were determined in a 4% aqueous dispersion of the hydrophobic oxide in water:methanol (1:1).

[0208] Reagents for pH determination:

[0209] Distilled water or completely deionized water, pH>5.5

[0210] Methanol, pa

[0211] Buffer pH7.00 pH4.66

[0212] pH value measurement equipment:

[0213] Laboratory scale (reading accuracy 0.1g)

[0214] Glass beaker, 250mL

[0215] Magnetic stirrer

[0216] Magnetic bar, 4 cm long

[0217] Combined pH Electrode

[0218] pH Measurement Equipment

[0219] Dispenser, 100mL

[0220] Procedure for determining pH value:

[0221] Determination according to the adaptation of DIN / ISO 787 / IX:

[0222] Calibration: Before determining the pH value, calibrate the measuring device with a buffer. If several measurements are carried out in succession, a single calibration is sufficient.

[0223] 4 g of the hydrophilic oxide was mixed into a paste in a 250 mL glass beaker with 96 g (96 mL) of water using a dispenser and stirred with a magnetic stirrer for 5 min while being immersed in a pH electrode (rmp about 1000 min -1 ).

[0224] 4 g of hydrophobic oxide was stirred into a paste in a 250 mL glass beaker with 48 g (61 mL) of methanol, and the suspension was diluted with 48 g (48 mL) of water and stirred for 5 min with a magnetic stirrer while immersing a pH electrode (rpm was about 1000 min-1). After turning off the stirrer, the pH was read after a 1 min standing time. The result was accurate to one decimal place.

[0225] D) Loss on drying

[0226] In contrast to the weighed amounts of 10 g mentioned in DIN ISO 787 II, a weighed amount of 1 g was used for the loss on drying determination.

[0227] The cover is put in place before cooling. No secondary drying is performed.

[0228] About 1 g of sample (accurate to 0.1 mg) was weighed into a weighing dish with a ground cover which had been dried at 105° C., avoiding the formation of dust, and dried in a drying cabinet for 2 h at 105° C. After cooling in the desiccator with its cover still on, the sample was reweighed under the blue gel.

[0229]

[0230] The result is accurate to one decimal place.

[0231] E) Loss on ignition

[0232] Equipment for determining loss on ignition:

[0233] Porcelain crucible with crucible cover

[0234] Muffle furnace

[0235] Analytical scale (reading accuracy is 0.1mg)

[0236] Dryer

[0237] Execute Loss on Ignition:

[0238] In contrast to DIN 55921, 0.3-1 g of undried substance (accurate to 0.1 mg) are weighed into a porcelain crucible with a crucible cover (the crucible cover has been preheated to red heat) and heated red hot in a muffle furnace at 1000° C. for 2 h. Care must be taken to avoid the formation of dust. It has proven to be advantageous to place the weighed sample into the muffle furnace while the muffle furnace is still cold. The slow heating of the furnace prevents the generation of stronger air turbulence in the porcelain crucible. After reaching 1000° C., red hot heating is continued for a further 2 h. Subsequently, the crucible cover is put in place and the weight loss of the crucible is determined on a blue gel in a desiccator.

[0239] Evaluation of loss on ignition determination

[0240] Since the LOI is measured relative to the sample dried at 105°C for 2 h, the following calculation formula is obtained:

[0241]

[0242] m0 = weighed amount (g)

[0243] TV = Loss on drying (%)

[0244] m1 = weight of the sample after heating to red heat (g)

[0245] The result is accurate to one decimal place.

[0246] F) Carbon content

[0247] The carbon content is determined by elemental analysis using a LECO C744 instrument. The measuring principle is based on the oxidation of the carbon in the sample to CO2, which is then quantified by an infrared detector.

[0248] G) SEM measurement

[0249] Energy dispersive X-ray spectroscopy (EDX) was performed with a SEM. For EDX mapping, a representative area of ​​the sample was used at a magnification of 1000× with an image width of 2048×1536 pixels (120μm×90.1μm), resulting in a pixel resolution of 0.059μm. The mapping was recorded with an accelerating voltage of 20kV. After the measurement, the sum-spectrum of the mapping was used to determine the elements present in the sample. The threshold of the image analysis was adjusted according to the semi-quantitative mass % value of each element.

[0250] Preparation of magnesium oxide:

[0251] Example 1: Preparation of magnesium oxide prepared by pyrolysis

[0252] 1.89 kg of an aqueous solution containing 1000 g of Mg(CH3COO)2*4H2O was prepared.

[0253] 2.5 kg / h of this dispersion and 15 Nm 3 / h air aerosol and sprayed into a tubular reaction with a combustion flame. The combustion gas of the flame is 8Nm 3 / h of hydrogen and 30Nm 3 / h of air composition. In addition, using 25Nm 3 / h of secondary air. After the reactor, the reaction gas is cooled and filtered.

[0254] The particle properties are shown in Table 1 and the TEM images of the particles are shown in Figure 1 In the XRD analysis ( Figure 2 ) showed that the main phase of the product was cubic MgO.

[0255] The resulting high surface area, pyrolytically prepared hydrophilic magnesium oxide has the physico-chemical property data shown in Table I.

[0256] Example 2: Preparation of surface modified magnesium oxide

[0257] 300 g of pyrolytically prepared magnesium oxide (Example 1) were placed in a mixer and sprayed with 72 g of octyltrimethoxysilane. After the spraying of the silane on the powder was complete, mixing was continued for another 5 min. The wetted powder was then tempered in an oven at 130° C. for 3 h. The surface-modified magnesium oxide formed had the physico-chemical property data shown in Table I.

[0258] The hydrophilic and surface-modified magnesium oxide has the physicochemical property data shown in Table 1.

[0259] Table 1:

[0260] nature Example 1 Example 2 <![CDATA[BET[m 2 / g]]]> 240 225 Compacted density [g / L] 56 78 pH 10.5 10.2 Loss on drying [%] 0.5 0.6 Loss on ignition [%] 12.2 17.6 Carbon content [%] 0.0 9.7

[0261] Examples of coated negative electrode active materials

[0262] raw material:

[0263] Dry coating additives:

[0264] The materials in Examples 1 and 2 above were used, i.e., the BET surface area of ​​Example 1 was 250 m 2 / g of fumed magnesium oxide and the BET surface area of ​​Example 2 is 230m 2 / g of fumed hydrophobic magnesium oxide (Evonik Operations GmbH). The fumed hydrophobic magnesium oxide of Example 2 was made hydrophobic by subjecting it to a hydrophobic treatment after the pyrolysis forming process as described above. A 65 m2 BET surface area purchased from Sigma-Aldrich, Germany, was also used.2 / g of non-fumed magnesium oxide as a comparative example. The non-fumed magnesium oxide is not nanostructured, but is a ground material having isolated non-aggregated particles.

[0265] Negative electrode active material:

[0266] A composite Si / C material made of 86 wt% carbon and 14 wt% silicon is commercially available under the trade name DXB8 Shandong GelonLib Co., Ltd., China, and is hereinafter referred to as Si86 / C14 matrix negative electrode active material ("Si86 / C14_AAM") powder or granules. As shown by SEM analysis, Si86 / C14_AAM is a mixture of SiOx and carbon and has the following characteristics.

[0267]

[0268] Example 3

[0269] Si86 / C14_AAM was mixed with the corresponding amount (1.0 wt%) of the fumed magnesium oxide of Example 1 in a high intensity laboratory mixer (SOMAKON mixer MP-GL with 0.5 L mixing unit). In order to homogenize the two powders, the speed was increased stepwise: 1 min 100 rpm, 1 min 200 rpm, 1 min 500 rpm. After homogenization, the mixing speed was further increased to 2000 rpm for 5 min to achieve a dry coating of the Si86 / C14_AAM particles by the corresponding magnesium oxide additive. The Si86 / C14_AAM particles were coated with a MgO coating with a thickness of 10-200 nm determined by TEM analysis. The Si86 / C14_AAM particles were coated with a uniform MgO coating with a thickness of 20-200 nm determined by TEM analysis.

[0270] Example 4

[0271] The process of Example 3 was repeated exactly, with the only difference being that the surface modified MgO of Embodiment 2 was used instead of the MgO of Example 1. The Si86 / C14_AAM particles were coated with a MgO coating layer having a thickness of 20-200 nm as determined by TEM analysis. When the fumed hydrophobic magnesium oxide of Example 2 was used as the coating additive, a uniform coating of the Si86 / C14_AAM particles was obtained, with a MgO coating layer having a thickness of 20-200 nm on top of the Si86 / C14_AAM particles.

[0272] Comparative Example 5

[0273] The procedure of Example 3 was repeated with the only difference being that a powder purchased from Sigma-Aldrich with a BET surface area of ​​65 m 2 / g of non-gas-phase process magnesium oxide replaces the gas-phase process MgO in Example 1.

[0274] When the fumed magnesium oxide of Examples 1 and 2 was used as the coating additive, uniformly coated active negative electrode particles were obtained, with a coating layer having a thickness of 20-200 nm on top of the Si86 / C14_AAM particles.

[0275] The particle size distribution of the hydrophilic magnesium oxide was measured to observe the dispersibility behavior during the application of shear force to the magnesium oxide agglomerates.

[0276] Figure 1 (a) shows the particle size distribution of the gas phase process MgO of Embodiment 1, Figure 1 (b) shows the particle size distribution of the non-fumed magnesium oxide used in Example 5 analyzed by a laser diffraction particle size analyzer. Figure 1 The x-axis in FIG. 5 shows the diameter of the particles, the left y-axis shows the volume % ("q%"), and the right y-axis shows the cumulative volume ("Q%").

[0277] The samples were dispersed in distilled water and treated in an external ultrasonic bath (160 W) for 15 min. For the fumed MgO of Example 1, an almost monomodal and very narrow particle size distribution was detected, with small aggregate sizes of d10 = 58 nm, d50 = 78 nm, d90 = 147 nm. In the case of non-fumed magnesium oxide, a slightly broader particle size distribution was detected, with much larger agglomerates of sizes d10 = 2680 nm, d50 = 4080 nm, d90 = 5950 nm, clearly indicating the presence of undispersed particles.

[0278] Analysis of coated anode materials by SEM-EDX

[0279] Figure 2 (2a, 2b and 2c) show SEM-EDX (scanning electron microscopy with energy dispersive X-ray) mapping of different magnesium oxide coating additives on Si86 / C14_AAM particles (a: gas phase hydrophobic MgO of Example 2, b: gas phase MgO of Example 1, c: non-gas phase magnesium oxide). Figure 2On the left side of each of a, 2b and 2c, a mapping of Si is shown to visualize the silicon distribution in the negative electrode active material (a mixture of carbon and silicon). This information helps to compare the Al / Ti distribution of the coating additive on the right, and well shows the interaction between the coating additive and the surface of the negative electrode material. The mapping (a) of Si86 / C14_AAM coated with gas-phase hydrophobic magnesium oxide shows complete and uniform MgO coverage around all negative electrode particles (silicon-rich and carbon-rich) basically. No large magnesium oxide agglomerates are detected, indicating that the dispersion of nanostructured gas-phase hydrophobic magnesium oxide is the most effective. In addition, no free unattached MgO particles are found next to the negative electrode particles, indicating that the surface-modified gas-phase magnesium oxide particles interact strongly with the Si86 / C14_AAM particle surface, and therefore have excellent adhesion between the coated MgO layer and the substrate.

[0280] Compared to the surface modified and thus hydrophobic fumed magnesium oxide, the hydrophilic fumed material of Example 1 shows fairly good agglomerate dispersion, but prefers to interact with silicon-rich particles rather than carbon-rich particles (b). Therefore, the magnesium oxide coating is more pronounced on the surface of the Si-rich particles. A small amount of undispersed and thus self-supporting fumed hydrophilic MgO particles that are not coated on the Si86 / C14_AAM particles are present in close proximity to the coated Si86 / C14_AAM particles.

[0281] In contrast, by using coarser magnesium oxide particles (non-fumed magnesium oxide) as a coating layer (c) for the Si86 / C14_AAM particles, only a small amount of finer sized MgO particles are attached to the surface of the Si86 / C14_AAM particles. Larger undispersed and therefore unattached MgO particles are located near the Si86 / C14_AAM particles, many of which are not fully coated. As a result, the Si86 / C14_AAM particles are not fully covered by this coarser, non-surface-modified and non-fumed MgO particles.

[0282] Thus, the Si86 / C14_AAM particles dry coated with fumed MgO show complete and uniform coverage of all Si86 / C14_AAM particles with MgO. No larger MgO agglomerates were detected, indicating good dispersibility of the nanostructured fumed MgO. In addition, no free, unattached MgO particles were found near the Si86 / C14_AAM particles. The surface-modified (i.e., hydrophobic) fumed MgO of Example 2 showed more uniform coverage of both carbon-rich and silicon-rich substrate particles than the non-surface-modified fumed MgO.

[0283] Figure 3A lithium ion battery, generally indicated by the numeral 10, is shown within a device 100 powered by a lithium ion battery 10 according to an embodiment of the present invention. The device may be any electronic device, such as a mobile phone, an electronic watch, a remote key, a laptop computer, a desktop computer, a tablet computer, etc. The device may also be an electrical device, such as a power tool, a vacuum cleaner, an electric lawn mower, an appliance, etc. The lithium ion battery 10 may be packaged in a module, each module having a plurality of lithium batteries 10, and used to power an electric vehicle or a hybrid vehicle. The lithium ion battery 10 includes a negative electrode collector 14 and a positive electrode collector 12, a positive electrode 18 adjacent to the positive electrode collector 12, a negative electrode adjacent to the negative electrode collector 14, an electrolyte 20, and a separator 22 disposed between the negative electrode 16 and the positive electrode 18. The negative electrode 16 includes a coated active negative electrode material, characterized in that the coated active negative electrode material is obtained by dry mixing the active negative electrode material and the nanostructured magnesium oxide produced by pyrolysis in a mixing unit. The active negative electrode material is in powder form and includes carbon particles, silicon particles, silicon oxide particles, or any combination thereof.

[0284] Although the invention has been described with reference to particular embodiments, it should be understood that the invention is not limited to these embodiments and that many variations will fall within the scope of the invention as defined by the appended claims.

[0285] Reference numerals list

[0286] ------------------------------------ 10 battery cells

[0287] 100 devices powered by battery cells

[0288] 12 Positive electrode current collector

[0289] 14 Negative electrode current collector

[0290] 16 Negative electrode

[0291] 18 positive electrode

[0292] 20 electrolytes

[0293] 22 Diaphragm

Claims

1. A method for preparing a coated active negative electrode material, characterized in that: The coated active negative electrode material is obtained by dry mixing the active negative electrode material and the nanostructured magnesium oxide produced by pyrolysis in a mixing unit under shear conditions, wherein the coated active negative electrode material is in the form of particles and the magnesium oxide has a particle size of 5-300 m 2 The BET surface area of ​​the particles is 1.3777:2014, and the average aggregate diameter d is determined by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25 ° C for 60 s. 50 The particle size distribution is unimodal and narrow, ranging from 5 to 150 nm.

2. The method according to claim 1, characterized in that (i) prior to the dry mixing, the pyrolyzed nanostructured magnesium oxide is surface treated to become hydrophobic by reacting the hydroxyl groups of the MgO with silane to form -O-Si-R groups, and (ii) the mixing unit has a specific electrical power of 0.05-1.5 kW / kg of the mixed negative electrode material.

3. The method according to claim 1 or 2, characterized in that: The average aggregate diameter d was determined by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25° C. for 60 s. 50 10-120nm, preferably 20-100nm.

4. The method according to claims 1 to 3, characterized in that As disclosed in the specification, energy dispersive X-ray mapping of scanning electron microscopy of the coated active negative electrode material provides complete and uniform MgO coverage around substantially all negative electrode particles.

5. The method according to claims 1 to 4, characterized in that The specific electrical power of the mixing unit is 0.1-1000 kW, and the volume of the mixing unit is 0.1 L to 2.5 m 3 , and the speed of the mixing tool in the mixing unit is 5-30m / s.

6. The method according to claims 1 to 5, characterized in that After a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution was sonicated for 60 s at 25° C., the span (d 90 -d 10 ) / d 50 It is 0.4-1.

2.

7. The method according to claims 1 to 6, characterized in that The active negative electrode material is in powder form and includes carbon particles, silicon particles, silicon oxide particles or any combination thereof.

8. The method according to claims 1 to 7, characterized in that The coated active negative electrode material is further subjected to heat treatment after the dry mixing.

9. The method according to claims 1 to 8, characterized in that Based on the total weight of the coated mixed negative electrode material, the proportion of the magnesium oxide in the coated active negative electrode material is 0.05wt%-5wt%.

10. A coated active negative electrode material, comprising an active negative electrode material of carbon particles, silicon particles, silicon oxide particles or any combination thereof, and a coating layer of nanostructured magnesium oxide produced by pyrolysis on the surface of the mixed negative electrode material, wherein the coated active negative electrode material is in the form of particles, and the magnesium oxide has a particle size of 5-300 m 2 The BET surface area of ​​the particles is 1.3777:2014, and the average aggregate diameter d is determined by static light scattering (SLS) after ultrasonic treatment of a mixture consisting of 5 wt % of the particles and 95 wt % of a 0.5 g / L sodium pyrophosphate aqueous solution at 25 ° C for 60 s. 50 The nanostructured magnesium oxide is preferably surface treated to become hydrophobic by reacting the hydroxyl groups of the MgO with silane to form -O-Si-R groups.

11. The coated active negative electrode material according to claim 10, characterized in that: As disclosed in the specification, SEM-EDX mapping of the coated active negative electrode material provides complete and uniform MgO coverage around substantially all negative electrode particles.

12. Coated active negative electrode material obtainable by the method according to claims 1 to 9.

13. An active negative electrode material for a lithium ion battery, comprising the coated active negative electrode material according to claims 10 to 12.

14. A lithium ion battery comprising the coated active negative electrode material according to claims 10 to 12.

15. Use of the coated active negative electrode material according to claims 10 to 12 in an active negative electrode material for a lithium ion battery.

16. A device comprising the lithium ion battery of claim 14, the device comprising an electrical or electronic device, the device comprising an electronic watch, a remote key, a laptop computer, a desktop computer, a tablet computer, a power tool, a vacuum cleaner, an electric lawn mower, an electrical appliance, and an electric vehicle.

Citation Information

Patent Citations

  • Silicon alloy nano-wire compound negative electrode material for lithium-ion battery and preparation method thereof

    CN106025242A

  • Protective coating for lithium-containing electrode and methods of making the same

    US20190363345A1

  • Lithium metal secondary battery featuring an anode-protecting layer

    US20190393543A1

  • Method for producing mixed oxide powder comprising lithium, lanthanum and zirconium

    WO2015173114A1

  • Method for manufacturing anodes for lithium-ion batteries

    WO2019215406A1